IMPROVING STUDENTS’ WRITING SKILL THROUGH MIND MAPPING AND FOUR SQUARE WRITING METHOD IN VIRTUAL LEARNING AT SMA NEGERI 1 PANGARIBUAN - Rini Saragih; Sondang Manik; Erika Sinambela; Arsen Nahum Pasaribu (Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of the research was to find out the improvement of students’ writing skills by using mind mapping and four square writing method. The design of the study was classroom action research by Kemmis and Taggart (2014). The subject of the study were 72 students of tenth grade, SMA Negeri 1 Pangribuan. The research findings were:1) the use of Mind Mapping and Four Square Writing Method in teaching writing skill had improved students’ writing skill. It was based on the fact that there was a significant increase of students’ scores in every cycle. It was also supported by the fact that increasing mean of students’ scores from pre-activity, cycle 1 and up to cycle 2. In Mind Mapping, the means of the total scores were 64.36, 74.5, and 79.47. In Four Square Writing, the means of scores were 66.25, 74.38, and 79.38. 2) Mind mapping and Four square Writing have contributed to the students’ motivation and enthusiasm in practicing English writing in classroom. Throughout interview and observation, it is found out that most students claim to be more active and responsive in writing class using Mind Mapping and Four Square Writing. Moreover, the students’ achievement in writing is much improved in terms of pronunciation, sentence structure, and the use of varied vocabularies. However, researchers still need to study more about the use of Mind Mapping and Four Square Writing Method in writing skills, especially in finding the best method in teaching writing with different settings and students’ level.